Identifikasi Sebaran Mangrove Melalui Pemanfaatan Citra Satelit Multi Spektral: An Identification of Mangrove Distribution using Multi-Spectral Satellite Imagery - Arif faisol; Mashudi Mashudi; Budiyono Budiyono; Risma Situngkir (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2026)
The Mangroves have been playing a crucial role, mainly serving both as plants and ecosystems. People have utilized mangroves for medicine, food, and other purposes. Remote sensing technology has been widely used for identifying and monitoring mangrove distributions. This study aims to identify mangrove distribution in Teluk Bintuni – West Papua by utilizing multi-spectral satellite imagery, i.e. Sentinel 2A. This research consists of 3 (three) main stages, i.e. data inventory, data analysis, and mapping of mangrove distribution. For this study, three scenes of Sentinel 2A satellite imagery acquired in 2022 were employed. The Mangrove Index was applied to identify the mangrove distribution. The research shows that the total mangrove in Teluk Bintuni is 257,671 Ha. or has decreased by 50 hectares compared to 2021. This decline is due to abrasion and mangrove logging activities driven by industrial purposes.